Halal Tourism Branding as a Key Determinant of Repeat Visits by Muslim Tourists in Mandalika - Ikhzam Khatami; Baiq Harly Widayanti; Agus Kurniawan (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This study examines the concept of Halal tourism branding as a key determinant of repeat visits by Muslim tourists to Mandalika. The Islamic concept of travel (safar/rihlah) is based on the commandment of Siirū fī al-ardḍ (walking on the earth) as a means of contemplation, aligned with the principle of Maqāṣid al-Sharīʿah (ḥifẓ al-dīn, or preservation of religion). Using a quantitative approach with 40 respondents who have visited at least twice, the regression results indicate that among the five factors, Halal Product Service (X2) is the most significant, exhibiting a positive and significant influence (p = 0.037) on the intention to revisit. This finding confirms that certified food and prayer facilities are essential for fostering religious commitment. Interestingly, Halal Service (X1) has a significant but negative influence (p = 0.034). Simultaneously, the overall model (F test) is not yet significant (p = 0.081), with an R² of 24.2%. The main conclusion emphasizes Halal Product Service as the primary determinant of revisit intention.